Purinergní P2X rodina a specifické vlastnosti P2X7 podtypu - Jindrichová, M; Zemková, H (Ceskoslovenska fysiologie, 2013)
Purinergic P2X receptors (P2XR), activated by extracellular adenosine 5'-triphosphate (ATP), represent a specific type of ligand-gated ion channels. They form functional trimeric homomers or heteromers which are nonselectively cation-permeable after receptor activation. P2X receptors are widely expressed in excitable and nonexcitable tissues and are involved in many physiological and pathophysiological processes such as platelet aggregation, contraction of smooth muscle, immune responses, cell proliferation and apoptosis or neurotransmission. In mammals, seven P2X subunits (P2X1-P2X7) have been identified. They differ mainly in distribution, pharmacological profile and kinetics of ATP-induced responses. The subtype P2X7 is the most specific in the P2X family and widely differs from other P2X subtypes.
Keywords: savci; Models, Molecular; purinergní receptory P2X7; adenosintrifosfát; Adenosine Triphosphate; Animals; Humans; lidé; zvířata; Mammals; molekulární modely; Protein Subunits; podjednotky proteinů; Receptors, Purinergic P2X7